PERILAKU SEKRETARIS BERKORESPONDENSI DIGITAL PADA PT ANGKASA PURA I BALI PERSPEKTIF TAKSONOMI BLOOM - I Gusti Lanang Suta; Anjli Purnama Sari; Made Ayu Jayanti Prita Utami; Cokorda Istri Sri Widhari (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2024)
Digital correspondence is an activity of creating, sending, receiving and replying to letters by utilizing digital communication technology. There were 41 respondents who filled out the questionnaire completely. The 41 respondents work as secretaries or do secretarial tasks. The observed behavioral domains of the research are based on the classification developed by Bloom, namely, knowledge, attitudes and practices. The analysis technique used in this study is multiple linear regression which aims to obtain an overall picture of the relationship between variables. Furthermore, using other analyze to interpret descriptive analysis data, classical assumption tests, and hypothesis testing partially and simultaneously. The results of the study show that knowledge, attitudes and practices have a positive and significant effect on secretary behavior in digital correspondence. Knowledge has a partial effect on Secretary Behavior in Digital Correspondence with a value of 9.204 > 1.683 Attitude has a partial effect on Secretary Behavior in Digital Correspondence with a value of 28.637 > 1.683 Practice has a partial effect on Secretary Behavior in Digital Correspondence with a value of 10.569 > 1.683 Knowledge, Attitudes, Practices simultaneously influence the Secretary's Behavior in Digital Correspondence with a value of 505.627 > 2.859. The predictive ability of these three variables on secretarial behavior in digital correspondence is 97.6 % while the rest is influenced by other factors outside the research model.